Optimization of installation and energy costs in water distribution systems with unknown flow directions. Issue 2 (3rd October 2022) - Cassiolato, Gustavo H. B.; Carvalho, Esdras P.; Ravagnani, Mauro Antonio da Silva Sá
Abstract: Water distribution networks (WDNs) are an important part of water distribution systems and are responsible for water transportation from the reservoirs to the demand nodes at adequate pressure and velocity. In the present paper, the synthesis of WDN is treated as an optimization problem with a mixed integer nonlinear programming formulation. The objective function to be minimized is the total network cost, considering installation and energy costs, with unknown flow directions, which is the novelty in the paper. Disjunctive programming and linearization techniques are used in the model formulation to avoid nonlinear and nonconvex problems. Two case studies are used to test the model's applicability. Results show that operational costs can represent a significant part of the total cost in sustainable networks. In the first case study, the total cost was better than the literature results (US$ 2, 272, 538.85 vs. US$ 2, 272, 387.49) and the operational costs represent ¼ of the total WDN costs. In the second case study, the operation cost corresponds to almost 2/3 of the total WDN cost. These results show the importance of considering operational costs in the WDN design. Also, the consideration of unknown flow directions can lead to better results for the network topology. HIGHLIGHTS: Water distribution systems design is treated as an optimization problem. The optimization problem has a mixed integer nonlinear programming formulation. Installation and energy costs are considered in the objective function. Flow directions in node demand loops are considered optimization variables. Operational costs can represent a significant part of the total water distribution cost.